Novel Nano‐sized bis‐indoline Derivatives as Antitumor Agents. (22nd November 2018) - Althagafi, Ismail I.; Abouzied, Amr S.; Farghaly, Thoraya A.; Al‐Qurashi, Nadia T.; Alfaifi, Mohammad Y.; Shaaban, Mohamed R.; Abdel Aziz, Mohamed R.
Abstract : Abstract : A facile access to novel bis ‐(indoline‐2, 3‐dione) was achieved via reactions of isatin with 1, 3‐dibromopropane. The utility of the versatile bis ‐(indoline‐2, 3‐dione) in the design of new multifunctional building blocks using condensation with hydrazine derivatives was demonstrated. Moreover, a new series of bis ‐thiazoles and bis ‐thiazol‐4(5 H )‐ones were synthesized by the reaction of bis ‐thiosemicarbazone derivative with various derivatives of hydrazonoyl halides. The calculations derived from X‐ray diffraction patterns indicated the nanosize of the newly designed compounds. The spectral data of the formed compounds were established their structures. Also, the cytotoxic activity of the produced derivatives was screened against line MCF‐7 (breast cancer cell). It was found that four derivatives from nine investigated compounds showed activity more potent than the standard drug used by 20 times in some cases.